Teachers’ Insights on Instructional Leaders: Understanding the Impact of Directors’ Practices on Motivation - Tep, Sopheng (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study consists of two main research objectives. The first objective is to assess the insights of teachers toward their school directors’ ILP and how these practices affect TEM. The second objective is to compare the insights of teachers toward their school directors’ ILP based on teachers’ demographic information. Methodology: The researcher uses quantitative reseach with a survey approach using descriptive statistics, independent sample t-test, and one-way ANOVA to address the research objectives. 295 state junior high school teachers who were pursuing higher education at a private university participated in this survey. Main Findings: The results indicated that teachers have high insights toward their school directors’ ILP (M = 3.94), and school directors’ ILP has a high influence on TEM (M = 4.22). Furthermore, the researcher discovered that gender and age did have significant effects on TEI toward school directors’ ILP, and levels of current study also significantly influences TEM (p < 0.05). In contrast, gender and TEM, age and TEM, levels of current study and ILP, teaching experience and ILP and TEM, do not have any significant effects (p < 0.05). Novelty/Originality of this study: These findings may provide significant keys to fostering TEM through effective ILP. In addition, these leadership practices enhance TEM within the Cambodian state junior high school context. Hence, school directors, academic staff and teachers can apply these findings in their duties in enhacing institutional’s success. Future research should incorporate diverse educational contexts and additional moderating variables to provide a more comprehensive understanding of the relationship between leadership behavior and TEM in other areas.